A self‐determination model of childhood exposure, perceived prevalence, justification, and perpetration of intimate partner violence. Issue 2 (21st January 2013) - Neighbors, Clayton; Walker, Denise D.; Mbilinyi, Lyungai F.; Zegree, Joan; Foster, Dawn W.; Roffman, Roger A.
Abstract The present research was designed to evaluate self‐determination theory as a framework for integrating factors associated with intimate partner violence (IPV) perpetration. The proposed model suggests that childhood exposure to parental violence may influence global motivational orientations which, in turn, results in greater cognitive biases (overestimating the prevalence of IPV and justification of IPV) which, in turn, contribute to an individual's decision to use abusive behavior. Participants included 124 men who had engaged in abusive behavior toward an intimate partner. Results provided reasonable support for the proposed model and stronger support for a revised model suggesting that controlled orientation, rather than autonomy orientation, appears to play a stronger role in the association between childhood exposure to parental violence and cognitive biases associated with abusive behavior.